Peptide Vaccination Against PD-L1 With IO103 a Novel Immune Modulatory Vaccine in Multiple Myeloma: A Phase I First-in-Human Trial - Jørgensen, Nicolai Grønne; Klausen, Uffe; Grauslund, Jacob Handlos; Helleberg, Carsten; Aagaard, Thomas Granum; Do, Trung Hieu; Ahmad, Shamaila Munir; Olsen, Lars Rønn; Klausen, Tobias Wirenfeldt; Breinholt, Marie Fredslund; Hansen, Morten; Martinenaite, Evelina; et al. (Frontiers in Immunology, 2020)
Background: Immune checkpoint blockade with monoclonal antibodies targeting programmed death 1 (PD-1) and its ligand PD-L1 has played a major role in the rise of cancer immune therapy. We have identified naturally occurring self-reactive T cells specific to PD-L1 in both healthy donors and cancer patients. Stimulation with a PD-L1 peptide (IO103), activates these cells to exhibit inflammatory and anti-regulatory functions that include cytotoxicity against PD-L1-expressing target cells. This prompted the initiation of the present first-in-human study of vaccination with IO103, registered at clinicaltrials.org (NCT03042793). Methods: Ten patients with multiple myeloma who were up to six months after high dose chemotherapy with autologous stem cell support, were enrolled. Subcutaneous vaccinations with IO103 with the adjuvant Montanide ISA 51 was given up to fifteen times during one year. Safety was assessed by the common toxicity criteria for adverse events (CTCAE). Immunogenicity of the vaccine was evaluated using IFNγ enzyme linked immunospot and intracellular cytokine staining on blood and skin infiltrating lymphocytes from sites of delayed-type hypersensitivity. The clinical course was described. Results: All adverse reactions to the PD-L1 vaccine were below CTCAE grade 3, and most were grade 1–2 injection site reactions. The total rate of adverse events was as expected for the population. All patients exhibited peptide specific immune responses in peripheral blood mononuclear cells and in skin-infiltrating lymphocytes after a delayed-type hypersensitivity test. The clinical course was as expected for the population. Three of ten patients had improvements of responses which coincided with the vaccinations. Conclusion: Vaccination against PD-L1 was associated with low toxicity and high immunogenicity. This study has prompted the initiation of later phase trials to assess the vaccines efficacy.